Spam Filtering With Dynamically Updated URL Statistics. - Jangbok Kim
Many URL-based spam filters rely on "white" and "black" lists to classify email. The authors' proposed URL-based spam filter instead analyzes URL statistics to dynamically calculate the probabilities of whether email with specific URLs are spam or legitimate, and then classifies them accordingly.
Keywords: Dynamically updated URL statistics; Email; Probability; Spam filtering